Aquatic Insects: Challenges to Populations Proceedings of the Royal Entomological Society’s 24th Symposium - Lancaster, Jill (CABI, 2014)
It is customary in the preface or introduction of a book to stress the importance of the subject matter, in order to justify the publication and to encourage readers on to the main text. One of the problems with this is the overuse, and consequent devaluation of ‘importance’ (Brooker et al., 2005). As far as aquatic insects are concerned, we feel that little justifi cation for having an interest in this group is necessary. Their persistent presence in the Earth’s fauna (>300 million years since insects invaded aquatic habitats), their numerical dominance in contemporary freshwaters (and some saline waters), and the diversity of roles they perform in aquatic ecosystems speak for the importance of the group. In an academic context, aquatic insects have served as model systems for the development of understanding of many aspects of insect physiology, behaviour, ecology and evolution, so there are many afi cionados of this group.